The role of adhering floral tissues in sclerotinia disease of kiwifruit - Hoyte, S. (New Zealand Plant Protection, 2000)
Field trials in 10 Bay of Plenty and two Waikato orchards during 1996/98 investigated the role of adhering floral tissues in the development of sclerotinia disease of kiwifruit caused by Sclerotinia sclerotiorum Petalfall and stamenfall extended over a period of at least six weeks S sclerotiorum was isolated from 053 of petals during flowering and 042 from adhering floral tissues on fruit Fruit from two orchards had a significantly higher incidence of fruit scarring on fruit with adhering floral tissues compared to fruit without adhering floral tissues The incidence of diseased fruitlets and fruit scarring was significantly reduced when floral tissues were physically removed after petalfall The data suggest that floral tissues are readily colonised by S sclerotiorum ascospores during flowering and that disease mostly arises directly from mycelial infection originating within adhering floral tissues This disease pathway will be exploited in developing disease management strategies